A Finite Element Analysis of the Stability of Composite Beams With Arbitrary Curvature - Mascolo, Ida; Modano, Mariano; Amendola, Ada; Fraternali, Fernando (Frontiers in Built Environment, 2018)
A finite element approximation of a theory recently proposed for the geometrically nonlinear analysis of laminated curved beams is developed. The application of the given finite element model to the computation of stability points and post-buckling behavior of beams with arbitrary curvature is also carried out, on taking into account the influences of shear deformation and warping effects on the in-plane and out-plane responses of the beam. The stability analysis is performed through a path-following procedure and a bordering algorithm. Several numerical results are given and comparisons with classical beam theories and other theories available in the relevant literature are established. The given results highlight that the proposed finite element model is well suited to study the stability of structures that incorporate laminated composite beams, such as, e.g., light-weight roof structures and arch bridges.